Pendampingan Peningkatan Kompetensi Kelompok Kerja Guru PJOK melalui Workshop Peraturan Pertandingan Karate dan Gizi Atlet di Jayapura - Ipa Sari Kardi; Muhammad Akbar Nurdin; Andi Syaiful; Junalia Muhammad; Nasruddin Nasruddin (Yayasan Literasi Sains Indonesia, 2025)
This community service programme was implemented in response to the need to enhance the competence of physical education teachers at the primary school level in developing karate skills among Papuan students. The Primary School Physical Education Teachers' Working Group (KKG) is a strategic forum for optimising the pedagogical and technical abilities of teachers in coaching young karate athletes who can compete in the National Student Sports Olympics (O2SN). The Papuan government aspires to revive the glory of Papuan sports, both domestically and internationally. The objective of this PKM is to improve the professional competence of elementary school PJOK teachers in Papua in coaching karate to achieve optimal performance at O2SN. This community service programme has successfully achieved its main objective of optimising the competence of the Papuan KKG PJOK SD in karate development. This community service programme utilised the Community-Based Participatory Research (CBPR) method. Significant improvements were observed in athletes' nutritional knowledge (77.4%), karate competition regulation competencies (89.6%), and teacher motivation levels (82.1%), which were categorised as high. Based on the results of this community service, it is hoped that Physical Education teachers will implement their knowledge and skills in coaching and preparing students for the O2SN Karate Sports competition.